Taburan sterol dalam sedimen di Sungai Sepang Besar, Selangor. - Mag Piah, Aminah; Mohd Ali, Masni; Zakaria, Mohamad Pauzi; Mohamed, Rahim (Universiti Kebangsaan Malaysia, 2008)
A study of sterol distribution in Sungai Sepang Besar was carried out on 17th September 2005 and 20th December 2005. Sediment samples were collected from 12 stations using grab sampler to determine the sources of sterol and the level of sewage contamination. Sterols were analyzed using Gas Chromatography-Mass Spectrometry. The results obtained showed that cholesterol and terrestrial plants (! -sitosterol and stigmasterol) dominated Sungai Sepang Besar while coastal areas were dominated by ergosterol. It is concluded that Sungai Sepang Besar was polluted with sewage based on coprostanol/cholesterol ratios.